A critical ethnography: the process of change at a core knowledge junior high school - Urban, Elizabeth A., author; Banning, James, advisor; Dickmann, Ellyn, advisor (Colorado State University. Libraries, 2008)
The challenge of educational change and the culture of organizational change have been the focus of research and literature for many decades. A look at the history of American education reveals that change designed in the direction of social fairness traditionally falls short of the objectives or fails completely within its first five years (Benham-Tye, 2000). The need for change and for continual renewal to improve schools is evident. The journey of change and the obstacles of that journey are more complex. The process of change and the puzzling dynamics of that process were the subject of this study. The purpose of the study was to further the understanding of the change process, the conditions which surround success and the obstacles which accompany failure. The focus of the study was a junior high school, which opened in the fall of 2004. An ethnographic study was conducted at the site over the period of the school's first sixteen months, from May 2004 to August 2005. The purpose of the first study was to record the journey of the school from its inception. In that first year, four key themes emerged: collaboration; visionary leadership; teachers and parents as agents of change; and trusting the process. That original study provided the archival data that were the starting point for the present study. The present study began in August, 2007 and continued through February, 2008. Research questions were designed to investigate the process of change over time. The qualitative research method was a modified version of Phil Carspecken's Model for Critical Ethnography (1996). The findings revealed additional cultural themes and dimensions as well as obstacles and barriers to the change process. New themes in year four. (1) The Journey of Change - From "Speed Boat to House Boat to Barge"; (2) Change Experienced by the Members - The Teacher's Stories; (3) From Trust the Process to Process the Trust - A Dose of Self-Scrutiny Four cultural dimensions. (1) Inquiry - Continual Study and Learning to Improve the Practice; (2) Responsibility - Speaking with Integrity and Doing What is Said; (3) Care - Practicing a Nurturing Pedagogy; (4) Celebration - Working Joyfully and Acknowledging Human Effort Obstacle to change. (1) Growth of School; (2) Fiscal Limitations; (3) Nature of the Profession; (4) Conventional Thinking Recommendations were made in the concluding chapter.
Keywords: change leadership; education change and reform; educational equity; junior high; organizational change; process of change; school culture; school administration; secondary education; middle schools; secondary schools; educational administration